Solid-phase organic syntheses. - Scott, Peter J. H. (Wiley, 2012)
"This series informs researchers of major accomplishments in solid-phase organic synthesis and provides actual experimental details and specific references. With this series, a reader will be able to sharpen hands-on skills by following the experimental procedures and refining understanding of the science by studying the chosen reactions. More importantly, this series guides readers in designing novel compound libraries, and may also inspire future breakthroughs. This second volume focuses on palladium chemistry in solid-phase synthesis, and discusses: palladium catalysts and reactions, procedures for preparation and utilization, ligands, and linker reactions"--